2019
DOI: 10.3390/app9204438
|View full text |Cite
|
Sign up to set email alerts
|

Soft Cationic Nanoparticles for Drug Delivery: Production and Cytotoxicity of Solid Lipid Nanoparticles (SLNs)

Abstract: The surface properties of nanoparticles have decisive influence on their interaction with biological barriers (i.e., living cells), being the concentration and type of surfactant factors to have into account. As a result of different molecular structure, charge, and degree of lipophilicity, different surfactants may interact differently with the cell membrane exhibiting different degrees of cytotoxicity. In this work, the cytotoxicity of two cationic solid lipid nanoparticles (SLNs), differing in the cationic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 37 publications
1
45
0
2
Order By: Relevance
“…We also observed that, at the lowest concentration, a drop of about 20% in cell viability occurred. This effect was attributed to the presence of CTAB in the formulations [36]. The further increase in z-Ave with the antibody attachment up to 327.33 ± 6.21 nm and decreasing of ZP down to 51.04 ± 6.21 mV confirmed the binding and formation of cPa-SLN-SAb complexes.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…We also observed that, at the lowest concentration, a drop of about 20% in cell viability occurred. This effect was attributed to the presence of CTAB in the formulations [36]. The further increase in z-Ave with the antibody attachment up to 327.33 ± 6.21 nm and decreasing of ZP down to 51.04 ± 6.21 mV confirmed the binding and formation of cPa-SLN-SAb complexes.…”
Section: Resultsmentioning
confidence: 67%
“…We also observed that, at the lowest concentration, a drop of about 20% in cell viability occurred. This effect was attributed to the presence of CTAB in the formulations [36].…”
Section: Resultsmentioning
confidence: 99%
“…The human intestinal Caco-2 cell line, a cell line derived from a colorectal adenocarcinoma, has a epithelial like-morphology and is commonly used as in vitro model for cytotoxicity screening of formulations intended for oral administration. In this work, the cell viability results, was tested in two time-points and using empty (blank) and loaded NLC, as recommended by Silva et al [68,69]. Results (Figure 4) demonstrate that both blank NLC and NLC loading sucupira oil are considered non-toxic.…”
Section: Resultsmentioning
confidence: 92%
“…Alpha-tocopheryl can also figure as oily phase in the composition of lipid nanoparticles [72]. It is important to bear in mind that the components of nanoparticles might be as toxic as the loaded bioactives [69]. In the present work, it is shown that the nanoparticle's components did not damage this cell line, in the range of tested concentrations (5,10,15, and 20 µg/mL, selected according to the literature [62]) as cell viability, at the highest concentration and 48 h exposure is about 95% of control (Figure 4, upper panel).…”
Section: Resultsmentioning
confidence: 99%
“…(as mentioned). The value of IC 50 (concentration that inhibits 50% of cell viability/proliferation or half maximal inhibitory concentration ) was calculated as reported by Silva et al [50]. Data analysis was performed using the software Statistical Program for Social Sciences (SPSS), version 20.0, as described in [49].…”
Section: Data and Statistical Analysismentioning
confidence: 99%